Distal Transradial Access in Anatomical Snuffbox for Coronary Angiography and Intervention: An Updated Meta-Analysis - Chendi Liang; Qinghua Han; Yongping Jia; Chunyu Fan; Gang Qin (Journal of Interventional Cardiology)
Objective. The previous meta-analysis has assessed that distal transradial access (dTRA) in anatomical snuffbox is safe and effective for coronary angiography and intervention and can reduce radial artery occlusion. However, since the publication of the previous meta-analysis, several observational studies have been added, so we performed an updated meta-analysis to include more eligible studies to compare distal transradial access in anatomical snuffbox with conventional transradial access (cTRA). Method. Pubmed, Embase, and Cochrane Library databases were searched for relevant studies from the literature published until 5 January 2021 to evaluate catheterization/puncture failure, hematoma, radial artery spasm, radial artery occlusion (RAO), access time, fluoroscopy time, radiation dose area product, total procedure time, and hemostatic device removal time. The pooled odds ratio (OR), weighted mean difference (WMD), and standardized mean difference (SMD) with 95% confidence interval (95% CI) were calculated for dichotomous and continuous variables, respectively. Results. A total of 9,054 patients from 14 studies were included in the meta-analysis, and we found no significant difference in catheterization/puncture failure (OR = 1.94, 95CI [0.97, 3.86], P=0.06), hematoma (OR = 0.97, 95CI [0.55, 1.73], P=0.926), radial artery spasm (OR = 0.76, 95CI [0.43, 1.36], P=0.354), total procedure time (SMD = 0.23, 95CI [−0.21, 0.68], P=0.308), or radiation dose area product (WMD = 216.88 Gy/cm2, 95CI [−126.24, 560.00], P=0.215), but dTRA had a lower incidence of RAO (OR = 0.39, 95CI [0.23, 0.66], P<0.001), shorter hemostatic device removal time (WMD = −66.62 min, 95CI [−76.68, −56.56], P<0.001), longer access time (SMD = 0.32, 95CI [0.08, 0.56], P=0.008), and longer fluoroscopy time (SMD = 0.16, 95CI [−0.00, 0.33], P=0.05) than cTRA. Conclusion. Compared with the cTRA, the dTRA has a lower incidence of radial artery occlusion and shorter hemostatic device removal time, which is worthy of further evaluation in clinical practice.